The learning cultures of organisations : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Human Resource Management at Massey University, Palmerston North, New Zealand - Ramsey, Philip L. (Massey University, 2003)
While there is significant interest in the area of learning organisations, research in this field has been fragmented. There is a need for an holistic model of learning organisations and a measurement system that can be used by both researchers and practitioners. This thesis applies Dilemma Theory as a means of meeting this need. An holistic model was developed based on a definition of learning organisations as ones that consciously seek to balance capacities with demands. In seeking this balance, an organisation will undertake a learning journey in which it encounters a variety of learning dilemmas: points where it must choose between alternative approaches to learning, each of which is attractive. In making these choices, learning-related values are established in the organisation. These values are the basis for a "learning culture" which shapes the way learning is understood and approached by the organisational community. Presenting people within an organisation with learning-related dilemmas allows learning cultures to be charted, thus providing the basis for a measurement system. Fifteen learning-related dilemmas were identified using three processes. Firstly, literature on learning organisations was reviewed to identify conflicts between metaphors used to explain the learning organisation. Secondly, a group of New Zealand consultants took part in a Delphi Technique process, in which they established criteria for identifying learning organisations and surfaced dilemmas embedded in the criteria. Finally, 'Culture Exploration Workshops' were conducted in three organisations to surface dilemmas experienced by business practitioners engaged in learning journeys. The 15 dilemmas identified were used to chart differences between 5 organisations. The measurement system was successful in identifying differences between organisations. Results were also consistent with values that might be expected from sub-cultures represented in the sample. The study concluded by outlining a programme of research aimed at refining the measurement system and applying it to the study of learning organisations.
Keywords: Organisational learning; Organisational culture; Fields of Research::350000 Commerce, Management, Tourism and Services::350200 Business and Management